Factors Determining Patient-Prosthesis Mismatch after Aortic Valve Replacement – A Prospective Cohort Study - Bonderman, Diana (Public Library of Science, 2013)
OBJECTIVE: “Patient-prosthesis mismatch” (PPM) after aortic valve replacement (AVR) has been reported to increase morbidity and mortality. Although algorithms have been developed to avoid PPM, factors favouring its occurrence have not been well defined. DESIGN AND SETTING: This was a prospective cohort study performed at the Medical University of Vienna. PATIENTS: 361 consecutive patients who underwent aortic valve replacement for isolated severe aortic stenosis were enrolled. MAIN OUTCOME MEASURES: Patient- as well as prosthesis-related factors determining the occurrence of moderate and severe PPM (defined as effective orifice area indexed to body surface area ≤ 0.8 cm(2)/m(2)) were studied. RESULTS: Postoperatively, 172 patients (48%) were diagnosed with PPM. The fact that predominantly female patients were affected (58% with PPM diagnosis in women versus 36% in men, p<0.001) was explained by the finding that they had smaller aortic root diameters (30.5±4.7 mm versus 35.3±4.2 mm, p<0.0001) and a higher proportion of bioprosthetic valves (82% versus 62%, p<0.0001), both independent predictors of PPM (aortic root diameter: OR 0.009 [95% CI, 0.004;0.013]; p = 0.0003, presence of bioprosthetic valve: OR 0.126 [95% CI, 0.078;0.175]; p<0.0001). CONCLUSIONS: The occurrence of PPM is determined by aortic root diameter and prosthesis type. Novel sutureless bioprostheses with optimized hemodynamic performance or transcatheter aortic valves may become a promising alternative to conventional bioprosthetic valves in the future.